Emergency department Modified Early Warning Score association with admission, admission disposition, mortality, and length of stay - Delgado-Hurtado, Juan J. (J Community Hosp Intern Med Perspect, 2016)
BACKGROUND: Geisinger Health System implemented the Modified Early Warning Score (MEWS) in 2011 and is fully integrated to the Electronic Medical Record (EMR). Our objective was to assess whether the emergency department (ED) MEWS (auto-calculated by EMR) is associated with admission to the hospital, admission disposition, inpatient mortality, and length of stay (LOS) 4 years after its implementation. METHODS: A random sample of 3,000 patients’ first encounter in the ED was extracted in the study period (between January 1, 2014 and May 31, 2015). Logistic regression was done to analyze whether mean, maximum, and median ED MEWS is associated with admission disposition, mortality, and LOS. RESULTS: Mean, maximum, and median ED MEWS is associated with admission to the hospital, admission disposition, and mortality. It correlates weakly with LOS. CONCLUSION: MEWS can be integrated to the EMR, and the score automatically generated still helps predict catastrophic events. MEWS can be used as a triage tool when deciding whether and where patients should be admitted.